Assessment of emergency department staff awareness, access and utilisation of advance care directives and goals of care: A cross-sectional survey. (September 2022) - Osman, Abdi D.; Howell, Jocelyn; Smithies, Lisa; Wilson, Damian; Lam, Louisa; Moran, Juli; Jones, Daryl; Taylor, David M.
Abstract: Background: Emergency department staff awareness, access and implementation of advance care directives and goals of care documents and the related patient consent processes are important but not well understood. Methods: A cross-sectional survey using purposive sampling was undertaken at a tertiary hospital's Emergency Department from 15th March to 26th April 2021. Participants were recruited through online platforms. Pre-validated questionnaires were distributed by email or as QR codes on bulletin boards. Data collected included staff: demographics, knowledge, access and implementation of advance care directives and goals of care documentation. Results: One hundred thirty-four (28%) of 476 targeted participants responded with nursing forming largest group. Results showed that previous attendance of advance care planning education was low at 20%. Familiarity with advance care directive documentations was only 19% while with goals of care document was average. 61 (48%) respondents reported ease of accessing electronic documents and 21 (19%) reported feeling very comfortable discussing and setting goals of care with patients ( p = <0.01 ). Conclusions: Staff awareness of advance care directive was poor, while awareness of goals of care was average. There was no association between advance care directives awareness and staff age group, gender, length of: - professional practice, practice at the study site.